Pengaruh MBKM, Budaya Kampus dan Prestasi Belajar Terhadap Kesiapan Kerja di Lembaga Keuangan Syariah : (Studi Kasus Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu Angkatan 2022) (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
This study examines the impact of MBKM, campus culture, and learning achievement on work readiness in Islamic financial institutions, specifically for students from the Faculty of Islamic Economics and Business at UIN Datokarama Palu, Class of 2022. Using a quantitative approach with descriptive research design, the study aims to analyze how these factors influence students' preparedness for work in the industry. The findings show that MBKM, campus culture, and learning achievement each have a positive and significant effect on work readiness. MBKM, with its emphasis on direct industrial experience, has the strongest impact, while campus culture shapes students' character and work ethics. Learning achievement reflects academic competencies essential for entering the workforce. The combined influence of these three factors was proven to significantly impact work readiness, with an F-value of 5.393, greater than the F-table value of 2.72. This demonstrates that work readiness stems from a combination of practical experience, acceptance of campus values, and academic success, all of which should be developed continuously.